Performance-enhancing drugs, supplements and the athlete’s heart - Pipe, Andrew (SA Heart Journal, 2017)
The use of performance-enhancing drugs is an unfortunatereality of contemporary sport. It would be a mistake tobelieve that this is a phenomenon found only in elite sport.Athletes at all levels and young adults may be tempted toaccentuate performance or physique with prohibited drugsor products marketed as supplements. No defined populationsof users ingesting known quantities of known substances are generally available for study. Many of these products have been associated with adverse health effects; cardiac structure and function are known to be affected by many of the products commonly abused. Changes to the lipoprotein profile, propensity for coagulation, coronary circulation, and ventricular function may accompany the use of many performance-enhancing compounds and methods. Anabolic steroids, other peptide hormones, stimulants, erythropoietin and blood doping, have all been associated with significant cardiovascular consequences. So-called nutritional supplements aggressively marketed to the athletically inclined, are available over the Internet and typically totally unregulated in the country of their origin. Clinicians should be aware of the problems that such drug use can engender, and be sensitive to the possibilities of such abuse in caring for athletes and young patients, particularly in those presenting with unusual or unanticipated cardiovascular signs and symptoms.